2016
DOI: 10.1002/adma.201600064
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Perovskite Nanocrystal Light‐Emitting Diodes Enabled by a Universal Crosslinking Method

Abstract: presence of aliphatic ligands. [ 7 ] These perovskite nanocrystals are highly luminescent and emit over the full visible range, making them ideal candidates for luminescent display applications. [ 6 ] The synthetic steps are generally straightforward, and the easy control of halide content allows the perovskite bandgaps to be tailored, both by chemical compositions as well as by quantum size effects. So far, perovskite nanocrystals are shown to have color-pure emission, close to unity photoluminescence yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
748
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 835 publications
(767 citation statements)
references
References 26 publications
14
748
2
3
Order By: Relevance
“…The additional perfluorinated ionomer layer both increased the hole injection efficiency of the device and suppressed the charging of the emissive layer, leading to a threefold increase in the peak brightness reaching 1377 cd m − 2 . Li et al 113 reported on LEDs comprising large (roughly 20 nm) square-shaped NCs with an electroluminescence QY of 5.7% using a device structure of glass/ITO/ZnO/CsPbX 3 QDs/ TFB polymer (poly[(9,9-dioctylfl uorenyl-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl) diphenylamine)])/MoO 3 (molybdenum trioxide)/Ag. Manna and colleagues 114 incorporated inorganic halide perovskite NCs of varying morphology (cubes and platelets) and halide composition (bromide and iodide) into white-light-emitting perovskite LEDs.…”
Section: Applications Of Perovskite Ncs Perovskite Ncs In Ledsmentioning
confidence: 99%
“…The additional perfluorinated ionomer layer both increased the hole injection efficiency of the device and suppressed the charging of the emissive layer, leading to a threefold increase in the peak brightness reaching 1377 cd m − 2 . Li et al 113 reported on LEDs comprising large (roughly 20 nm) square-shaped NCs with an electroluminescence QY of 5.7% using a device structure of glass/ITO/ZnO/CsPbX 3 QDs/ TFB polymer (poly[(9,9-dioctylfl uorenyl-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl) diphenylamine)])/MoO 3 (molybdenum trioxide)/Ag. Manna and colleagues 114 incorporated inorganic halide perovskite NCs of varying morphology (cubes and platelets) and halide composition (bromide and iodide) into white-light-emitting perovskite LEDs.…”
Section: Applications Of Perovskite Ncs Perovskite Ncs In Ledsmentioning
confidence: 99%
“…[12][13][14][15][16][17] The vast majority of research conducted in this area has focused on "first generation" MAPbX 3 -based perovskites, [8,18] mainly due to the excellent tunability of their optoelectronic properties. [18,19] Characteristics such as high mobility, [20,21] high bimolecular recombination rate for charge carriers, [10] and low exciton binding energy [22][23][24] have resulted in the demonstration of high-performance films and devices for PV, LED, [9,12,[25][26][27] FET, [21] and lasing applications. [10,28] One potential drawback of the MAPbX 3 semiconductor family, however, is its relatively wide bandgap (3.2-1.6 eV), which dramatically limits its sensitivity in the near-IR (NIR) to mid-IR region of the solar spectrum.…”
Section: Doi: 101002/adma201604744mentioning
confidence: 99%
“…With these crystals, full-colour PeLEDs can be fabricated, and their photograph and emission spectra are shown in Figure 3(c). 30,39,40 After the report of Protesescu et al, Zhang et al reported the synthesis of organic-inorganic hybrid perovskite quantum dots with PLQEs up to 70% and demonstrated the application of them as an alternative phosphor for white-light LEDs. 41 Afterwards various synthesis routes have been reported.…”
Section: B Halide Perovskite Emitter Layers Prepared From Nanocrystamentioning
confidence: 99%